Strategi Muhammadiyah Boarding School Klaten dalam Mengatasi Bullying di Kalangan Santri - Utama, Angga Pria; Salim, Hakimmudin (Institut Agama Islam Daruttaqwa Gresik, 2024)
Bullying remains a serious issue in educational institutions, including Islamic boarding schools, due to its negative impact on students’ psychological, social, and spiritual development. Although pesantren are known for their strong emphasis on religious and moral values, bullying still occurs in various forms verbal, physical, and psychological. This indicates a gap between value education and its practical application in daily life. This study aims to analyze the strategies implemented by Muhammadiyah Boarding School (MBS) Klaten in addressing bullying among students. Using a qualitative approach, data were collected through observation, interviews, and documentation. The findings reveal that the causes of bullying include internal factors, such as students’ introverted or aggressive traits, and external factors like a culture of seniority. MBS Klaten has adopted several preventive strategies, including confidential reporting mechanisms, education about the dangers of bullying, close supervision by dormitory supervisors (musyrif), and counseling services. These strategies have proven effective in creating a safe, inclusive environment that supports students’ character development. The implications of this study highlight the need for faith-based educational institutions to develop a comprehensive and systemic approach to bullying prevention beyond moral instruction alone. Strengthening collaboration among caregivers, teachers, and counselors is essential to build a responsive detection and intervention system. Additionally, promoting a culture of empathy, compassion, and care should be integrated into all aspects of student life as part of sustainable character education.